Arachis Bioassay for Soil Contaminated with Hexavalent Chromium - P. Kumar2, A. Saravanakumar2, A. Aslam2, A. Shahjahan2 and R. Ravikumar2, ReviewK. Rajalakshmi1* (Recent Research in Science and Technology, 2010)
Heavy metals evoke multiple direct and indirect effects on plant growth and affect many physiological functions. Negative impacts include inhibition of seed germination, reduction in plant growth and yield and metabolic disturbances evaluated in terms of altered biochemicals. In vitro and pot culture studies revealed that there is a significant uptake of Chromium by natural growth conditions. There was also a strong negative correlation between the concentration of Cr(VI) and the biomass production in A. hypogea. The control plant grows tall than any other Chromium treated plant. The paper wig method (Whattman filter paper number 3) was found to be effective in screening the Cr(VI) absorption. Interestingly, Chromium in mild concentrations is promoting the cellular elongation resulting in the longest root of seedlings reared in the 1mM hexavalent Chromium. Chromium when supplemented with the selected bioinoculants to the experimental formulations showed promising results in the plant growth and development than the control seedlings. Both pot cultured plants and in vitro raised plants were found to contain 375.80 ppm (per 5g) and 47.06 ppm (per 5g) of Chromium respectively in the Atomic Absortion Spectrometric quantifications. Further experiments are underway to study the biological effects and accumulation of absorbed Cr(VI) in this economically important legume.